Pneumothorax following endobronchial valve therapy and iIts impact on clinical outcomes in severe emphysema - Gompelmann, Daniela; Herth, Felix; Slebos, Dirk Jan; Valipour, Arschang; Ernst, Armin; Criner, Gerard J.; Eberhardt, Ralf (Respiration, 2014)
Background: Patients who achieve significant target lobe volume reduction (TLVR) following endobronchial valve (EBV) treatment may experience substantial improvements in clinical outcome measures. However, in cases of rapid TLVR, the risk of pneumothorax increases due to parenchymal rupture of the adjacent untreated lobe. Target lobe collapse may be more likely in EBV-treated patients who have low collateral ventilation. Objectives: The aim of this study was to evaluate the impact of pneumothorax on outcome following EBV treatment. Methods: Data from three prospective clinical trials (the US and European cohorts of VENT and the Multicenter Chartis study) were retrieved for the analysis. All patients had undergone chest X-ray within 24 h of EBV implantation to explore the presence of pneumothorax. TLVR was assessed at either 30 (Chartis study) or 180 days (VENT), and clinical outcome measures (forced expiratory volume in 1 s (FEV1), St. George's Respiratory Questionnaire (SGRQ) and 6-min-walk distance (6-MWD)) were assessed 180 days after implantation. Results: The overall rate of pneumothorax following valve therapy was 5.9% (25/421). Among these patients, 68% had a prolonged air leak for >7 days. However, patients who experienced a pneumothorax benefitted from EBV therapy, with a mean TLVR of 65% (n = 20). The mean percent change in FEV1 was 15 ± 15%, and the mean change in SGRQ was -7 ± 12 points. Conclusions: Although pneumothorax is a complication of EBV placement, it does not appear to have a negative impact on clinical outcome in terms of FEV1 and health-related quality of life.